Maximum allowable damage approach to fire safety performance quantification - Cadena, Jaime E.; McLaggan, Martyn; Osorio, Andres F.; Torero, Jose L.; Lange, David (Fire safety journal, 2022)
Risk assessments are used to inform decision-making in hazardous systems. The process involves highly technical steps such as quantifying uncertainty and it is typically carried out by subject matter experts with a robust engineering background. The process also involves value-loaded steps such selecting the risk acceptance criteria for evaluating the risks. In the built environment, risk assessments support performance-based design and of late, these have been increasingly framed as the preferred option to quantify and demonstrate adequate fire safety performance. This argument is supported by the assumption that risk is an adequate proxy for fire safety goals. The present work puts forward a counterargument, stating that fire safety performance should be mainly defined as a function of fire consequences, avoiding the use of fire risk assessments as a proxy to fire safety goals. An alternative fire risk assessment methodology is introduced based on the concept of maximum allowable damage, which is exemplified in a combustible façade residential building case-study. The methodology presented here aims at building upon the knowledge and tools of fire safety engineering to obtain more trustworthy risk assessments and therefore attain a safer built environment.